tudy of the Role of the Outer Membrane Proteins of Serratia marcescence in Resistant to Antibiotics - Yossef, H. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
After diagnostic tests on ten isolates of S. marcescence, were made an examination of sensitivity to various antibiotics and checking the ability to produce Î²-lactamase of all isolates.        The outer membrane protein quantity was determined in Î¼g/cm3 for all isolates. The results showed that S. marcescence have antibiotic multiresistant and all isolates had the ability to produce Î²-lactamase and its resistance may arise from more than two mechanisms like overproduction of antibiotic inactivation enzymes and the decrease of permeability by outer membrane protein.